2022
DOI: 10.21203/rs.3.rs-1393907/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Shorter- and Longer-Term Mortality after COVID-19 Presentation among Dialysis Patients: Parallel Use of Machine Learning Models in Latin and North American Countries

Abstract: Background: We developed machine learning models to understand the predictors of shorter-, intermediate-, and longer-term mortality among hemodialysis (HD) patients affected by COVID-19 in four countries in the Americas. Methods: We used data from adult HD patients treated at regional institutions of a global provider in Latin America (LatAm) and North America who contracted COVID-19 in 2020 before SARS-CoV-2 vaccines were available. Using 93 commonly captured variables, we developed machine learning models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our study found that albumin lower than 36.8g/L was a risk factor for pneumonia in MHD patients with COVID-19. Guinsburg et al [11] found that malnutrition (low albumin and creatinine in the past) was one of the main predictors of death in patients.…”
mentioning
confidence: 99%
“…Our study found that albumin lower than 36.8g/L was a risk factor for pneumonia in MHD patients with COVID-19. Guinsburg et al [11] found that malnutrition (low albumin and creatinine in the past) was one of the main predictors of death in patients.…”
mentioning
confidence: 99%